An Event-B-based approach to hybrid systems engineering and its application to a hemodialysis machine case study. (December 2018) - Buga, Andreea; Mashkoor, Atif; Nemeş, Sorana Tania; Schewe, Klaus-Dieter; Songprasop, Pornpan
Highlights: The paper presents a conceptual modeling for hybrid systems engineering capture structure constraints and behavior. The model combines ER-based concepts with Event-B. The paper contains an application case study. Abstract: Systems engineering concerns the complete process for the development of complex systems comprising hardware, software, facilities and personnel. Such systems are hybrid, as some components are characterized by continuous behavior, whereas the behavior of others is discrete. In this paper we present a concise conceptual model for hybrid systems engineering with semantics grounded in a hybrid extension of Event-B. We show that structural modeling can be based on well-known concepts of the entity-relationship model requiring only some extensions to data types and constraints, while behavioral modeling requires a careful separation of synchronous and asynchronous interaction and high-level means for the integration of continuous functions. On these grounds we address the separation of concerns for continuous and hybrid components. The article uses a sophisticated industrial example of a hemodialysis machine to illustrate the modeling method.